Perancangan Aplikasi Fakultas Kedokteran Universitas Indonesia Berbasis Web Menggunakan Bahasa Pemrograman PHP dan Database MySQL - Hari Setiyani; Hasfhi Tobing (JI-Tech, 2020)
At this time Medical Faculty in University of Indonesia still using the manual system, a manual system here means a system that still uses hand writing method without the slightest untouched computer technology. This will only slow the Interaction between the Academic Staff and the Students for example. In this study an information system will be built using a web-based online publication that media will be built, is designed such that it can process data, storage of data, and disseminate information quickly and accurately is intended only for within the scope of the Medical Faculty in University of Indonesia itself. In this research the scope will build an Information System using the Web as the Online based, so that it can process data, storage data, and can disseminate information quickly and accurately which is intended only for within the scope of the Faculty of Medicine in the University of Indonesia.